2013
DOI: 10.1371/journal.pone.0070966
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic, Spatial and Temporal Patterns of Bleaching in Anemones Inhabited by Anemonefishes

Abstract: BackgroundRising sea temperatures are causing significant destruction to coral reef ecosystems due to coral mortality from thermally-induced bleaching (loss of symbiotic algae and/or their photosynthetic pigments). Although bleaching has been intensively studied in corals, little is known about the causes and consequences of bleaching in other tropical symbiotic organisms.Methodology/Principal FindingsThis study used underwater visual surveys to investigate bleaching in the 10 species of anemones that host ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Amphiprion clarkii was the only species that spent equal time in cues from unbleached or bleached hosts versus seawater. Because host anemones are typically rare on reefs [20,[46][47][48][49], anemonefishes have relatively short pelagic larval durations of 7-22 days [50][51][52], and predation pressure is likely to be high during this time; settling on the first host encountered, even if bleached, may be beneficial as rejecting bleached habitat may mean that settlement does not occur. Our study provides laboratory-based comparative observations and insights into how anemonefishes may respond to bleaching, which are further supported by field observations, as Saenz-Agudelo et al [19] found no evidence of A. polymnus larvae avoiding bleached anemones in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Amphiprion clarkii was the only species that spent equal time in cues from unbleached or bleached hosts versus seawater. Because host anemones are typically rare on reefs [20,[46][47][48][49], anemonefishes have relatively short pelagic larval durations of 7-22 days [50][51][52], and predation pressure is likely to be high during this time; settling on the first host encountered, even if bleached, may be beneficial as rejecting bleached habitat may mean that settlement does not occur. Our study provides laboratory-based comparative observations and insights into how anemonefishes may respond to bleaching, which are further supported by field observations, as Saenz-Agudelo et al [19] found no evidence of A. polymnus larvae avoiding bleached anemones in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Subordinate individuals tend to occupy the peripheral areas of the anemone [42], as occurs in intraspecific groups where competition forces subordinates to occupy suboptimal and less favourable environments [38][39][40]. Dominant species from interspecific social groups generally did not alter their spatial distribution within the host anemone, although the common dominant species A. clarkii increased the time it spent outside of the host anemone.…”
Section: Discussionmentioning
confidence: 92%
“…It is susceptible to bleaching over large geographical scales, although the percentage of naturally bleached anemones is usually in the range of 1–4% (Frisch & Hobbs ; Hobbs et al . ). Adult H. crispa are typically 20–25 cm in size (oral disc diameter) and light tan to brown in colour, with sinuous tapered tentacles (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 of Hobbs et al . ), so by putting a black plastic sheet over the relevant part of each crevice, we were able to block direct sunlight to each anemone whilst still allowing for horizontal movement of water. Some physical contact between the plastic sheets and anemone tentacles was inevitable, but this was minimized in the sense that we tried to block sunlight from above rather than encapsulate the anemones within the plastic sheets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation